Conceptualizing social structure: A reorientative discussion based on persistent paradoxical debates - Karim, A.H.M Zehadul (Kamla Raj Enterprises, 2016)
Social structure is the most fundamental and major concept in Sociology and Social Anthropology and for that reason, the theorists have consistently argued that if we want to understand the social system and social relationship in human society, then certainly we have to be very clear about the concept of social structure without having any ambiguity of it. There are a myriad of definitional references on social structure with persistent paradoxical debates, which are clarified in this paper through the writings and enunciation of sociologists and social anthropologists with referential sequences of time. While the concept of social structure has received theoretical treatise through the writings of different scholars and theoreticians, many empiricists however, have narrated the concept from their own field-based ethnographic details at the micro-level investigations, viewing that all forms of social interactions and activities occur within the framework of social structure in the societal and community contexts. This paper thus generates a cumulative number of critical discussions both at the theoretical and empirical spheres of sociological literature stemming towards developing its own paradigmatic thinking of social structure.